A Bibliometric Study Investigating the Emerging Digital Behaviour Trends in Education: Implications for Teaching and Learning Practices - Trihantoyo, Syunu; Achmad Supriyanto; Amrozi Khamidi; Muhammad Faizal Bin A. Ghani; Muhamad Sholeh (Universitas Pendidikan Ganesha, 2024)
Recent studies have indicated a significant increase in the investigation of digital behaviour in education, coinciding with the advent of distance learning in the aftermath of the global pandemic. The objective of this study is to analyse contemporary research trends on digital behaviour in education through bibliometric analysis of data sourced from Scopus. This research method employs a literature review with bibliometric analysis.The research stage was conducted by determining: (i) the purpose and scope of the study, (ii) bibliometric study techniques, (iii) data collection, (iv) data analysis, and (v) reporting findings.Data analysis was carried out by determining keywords in the data collection process, namely